Fatores de influência da escolha de uma instituição de ensino superior por jovens do Maciço do Baturité - Maia, Glaucilene Lima (2015)
This research aimed to analyze how the process of choosing an IES - Higher Education Institution, by students that are finishing high school in the region of Baturité Massif occurs, as well as to identify which of the educational marketing actions developed by IFCE Campus Baturité help in this process. It presents a theoretical survey of educational marketing and marketing activities in IES, highlighting the importance of strategic marketing planning and market research in order to stimulate students interest in choosing IFCE Campus Baturité and also strengthen the relationship of the Institution with the community. The research was carried out in the region of Baturité Massif and at IFCE Campus Baturité. The researched population consisted of state high school students in the 3rd year in all of the 13 cities of Baturité Massif. The sample selected considered the number of questionnaires answered by students of the seven state high schools reseached in the cities of Aratuba, Baturité, Guaramiranga, Mulungu, Pacoti, Palmácia and Redenção, totaling 542 students. The research presents the following methodological aspects: it is inductive, qualitative and quantitative. According to the objectives, it is a descriptive research. This is a field research with the application of two questionnaires. Semi-structured interviews were held with two representatives of IFCE, the Director of IFCE Campus Baturité and the Head of Rectory's Social Communication Department as a way to deepen the studies on the issue and also supporting or confronting the data collected in the questionnaires. The analysis of the results presented a relevant data in order to create an educational marketing action plan to strengthen the brand of IFCE in the region of Baturité Massif, as well as bringing the institution closer to the community. The research revealed that many young people do not choose IFCE because they do not have enough information about the institution, and / or they do not want to take the courses offered by IFCE Campus Baturite. The absence of more effective and consistent actions of educational marketing by IFCE Campus Baturité are the possible causes for the high number of unfilled vacancies in the Campus. According to research, the factor that most influences the choice of a IES - Higher Education Institution by the youths of Baturité Massif is the "Perspective of future employment: Recognition of professional qualifications by future employers". By analyzing the data it is possible to conclude that IFCE Campus Baturité's educational marketing actions must undergo an urgent restructuring.